Multi‐agent control in modular motor drives by means of gossip consensus - Lynn Verkroost; Frederik De Belie; Peter Sergeant; Hendrik Vansompel (IET Electric Power Applications, 2022)
Abstract A modular motor drive (MMD) can be considered as a multi‐agent system, in which the agents work together to reach a common goal. One agent in such an MMD comprises only a subset of the concentrated windings and power electronic converter modules and is equipped with an independent controller. The goal of this research is to let the agents cooperate to distribute a torque demand among them in a completely decentralised way, in order to comply with the flexibility and reliability of modular motor drives. However, the current condition of each agent must still be taken into account during this torque allocation. To limit the communication load, only communication between neighbouring agents is allowed. The combination of a gossip consensus algorithm and multiple decentralised PI current controllers is used for this purpose. Simulations and experimental results on a modular axial‐flux permanent magnet synchronous machine consisting of five agents confirm that the total torque demand is delivered under the proposed control strategy, even during agent malfunctions, under random communication link failures and with non‐identical agents.